Immunopathology of the lens. I. Humoral and cellular immune responses to heterologous lens antigens and their roles in ocular inflammation. Issue 3 (March 1977) - Rahi, A. H.; Misra, R. N.; Morgan, G.
Abstract : In experimental rabbits heterologous soluble lens proteins consisting of alpha-, beta-, and gamma-crystallins were found to be antigenic; they stimulated a marked antibody response compared to a rather weak T-cell response. The serum antibodies to alpha-crystallins appeared first, to be followed by antibodies to beta- and gamma-crystallins in that order. The rabbits did not respond to heterologous gamma-crystallins unless these were injected with Freund's adjuvant containing mycobacteria. Incomplete Freund's adjuvant (i.e., without mycobacteria) was found to be an inferior immunoaccelerator so far as lens antigens are concerned. The response to lenticular antigens in both magnitude and duration varied in different rabbits, which suggested to us the important role played by a central control mechanism involving the immune response (Ir) genes. Some of the antibodies in potent lens antisera cross-reacted with mitochondria, endoplasmic reticulum (i.e., microsomes), contractile organelles, and cell nuclei. This explains for the first time at least in part the reasons for the widely observed phenomenon of the reactivity of lens antisera with ocular and extraocular structures. Antibodies to soluble lens proteins as detected by immunofluorescence and immunoperoxidase techniques were shown to be of the IgG class. Systemic heterologous immunisation followed by discission of the lens does not lead to the typical changes of phakoallergic endophthalmitis in the rabbit.